Passive House Design: Planning and design of energy-efficient buildings - Gonzalo, Roberto; Vallentin, Rainer (DETAIL Green Books, 2014)
"Passive House Design" provides architects with the confidence required to deal with the Passive House Standard. It shows where there is significant scope for design and explains design strategies that lead to better passive houses. A selection of international buildings illustrate how design, construction and building technology combine in passive houses. Chapters on building physics, building services engineering and energy balancing round out the planning guidelines.